Effects of increased mortality on gorgonian corals (Cnidaria, Octocorallia): different demographic features may lead affected populations to unexpected recovery and new equilibrium points - Santangelo, G; Cupido, R; Cocito, S; Bramanti, L; Priori, C; Erra, F; Iannelli, M (Hydrobiologia, 2015)
Over the last years, several marine populations suffered a drastic mortality increase of different origins; assessing the changes occurring in the demographic structure of such populations will allow evaluating their future trends and their ultimate fate. The aim of our research was to assess main demographic descriptors and related dynamics in populations of the Mediterranean gorgonians Paramuricea clavata and Corallium rubrum (the “precious red coral”) both subject to increased mortality, by life-history tables and Leslie-Lewis transition matrices. Gorgonian populations have been generally been considered to have low recruitment and low dynamics. Here, we test whether these features change when mortality rises and if such populations can reach new equilibria? Our findings show large differences between the two species examined, with lower recruitment and adult colony density, shorter life-span but over-abundant reproductive output in P. clavata. Recruitment density dependence was found in crowded populations of both species, albeit with different trends. Populations of both species tend to recover even after drastic mortality increase and P. clavata reaches a new equilibrium at lower densities than at pristine values, and this in a few years time. The findings in this review could shed some light on the poorly understood dynamics occurring in deep-water dwelling, affected populations of long-lived and slow-growing gorgonian corals.